Pemulihan Trauma Pasca Bencana pada Tokoh Anak dalam Buku Cerita Bergambar (E Hon) - Irfana, En Nahl Al Atiqo Sanabila; Damayanti, Silvia; Ari Sulatri, Ni Luh Putu (Humanis; Vol 26 No 1 (2022)DO - 10.24843/JH.2022.v26.i01.p09, 2022)
This study aimed to know the form of trauma recovery for child survivors after the 2011 T?hoku Tsunami, in the picture book (e hon) entitled   Minna de Utau be!  by Mari Mitsuoka. The method used in this research is descriptive analysis. Theories used in this research are Sigmund Freud's theory of Literature Psychology and Resilience theory by Masten (2014). The analysis results showed that child characters in e hon are described as having characteristics of mild trauma that can recover quickly through appropriate trauma recovery support. Those types of recovery support were affected by protective factors that interconnect and complement each other, such as the characteristics of child survivors, family support, and psychological support activities in the school and community environment. The effectiveness of appropriate recovery aid enhances children's resilience in the trauma recovery process, so they can recover and thrive after experiencing a natural disaster.